Possible trends in modern Russian philosophy and social science of physical culture and sports - Donskikh K.Y. ,; Kotusov D.V. ,; Arzamastseva N.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to highlight and discuss the probabilistic trends in modern Russian social philosophy and the science of FKiS, starting in the 90s of the XX century. laid by the next wave of "Eurocentrism" and "Westernization" of the domestic information space. Methods and structure of the study. The study is designed as a systematic comparison of generally accepted and innovative scientific approaches in the fields of philosophy, social and cultural anthropology, history, political economy, political science, sociology, psychology and pedagogy of physical culture and sports. Results and conclusions. The current state of Russian philosophy of physical culture and Sport (FKiS), as well as related social sciences, is characterized by sustained conservatism, insufficient preparedness and adaptation to a number of significant changes. This concerns the transition of Russian society to a capitalist model of development, the increasing informational impact of Western (European and American) scientific, educational and cultural trends, the aggravation of the international situation and foreign policy contradictions, as well as the transformation of the role and social significance of elite and Olympic sports in modern reality. Due to the objectivity and inevitability of historical progress, there is an urgent need for an urgent and fundamental restructuring of philosophy and social sciences studying the FKiS. This is necessary to ensure their compliance with modern socio-cultural challenges and the ability to adequately understand and cover them.